The incidence of Faith Popcorn's consumer trends among North-West University staff - Claassen, Vivian (University of the Free State, 2007)
Marketers have realised that the consumer needs to be the central focus of the organisation’s activities. In the United States of America a marketing expert, Faith Popcorn, has done valuable research on consumer trends. Popcorn proposed that if marketers keep these consumer trends in mind when developing and marketing products or services, they will address the needs of consumers more effectively. A limited amount of research on consumer trends have been done in South Africa and according to the researcher’s knowledge, no research on Faith Popcorn’s trends specifically. The aim of this study was firstly to determine whether ten consumer trends identified by Popcorn in 1991 occurred among the staff members of the North-West University (NWU), and secondly to work towards recommending points of departure for the application of this knowledge in integrated marketing communication (IMC). In the context of a selected group of people, Faith Popcorn’s consumer trends were addressed by the following research question: Do the ten consumer trends identified by Faith Popcorn in the American marketplace also occur among the permanent staff members of the NWU? And if so, how can knowledge about these trends be used to formulate more effective IMC strategies? All permanent staff members of the NWU participated as respondents. A self-administered questionnaire was developed and used as a data-collection method. The questionnaire was developed to determine whether the consumer trends of Cocooning, Fantasy Adventure, Small Indulgences, Egonomics, Cashing Out, Down-Aging, Being Alive, The Vigilante Consumer, 99 Lives and Save our Society occurred among the respondents. The results were analysed by means of the following statistical methods: (i) factor analysis with varimax orthogonal axe rotation; (ii), Cronbach’s alpha coefficient, to obtain an index of the internal consistency of the factors and (iii) effect sizes, to determine practical significance between the factors and demographic variables. The factor analysis revealed that 8 of the 10 consumer trends grouped together and measured the appropriate variables. It was found that 2 of the 10 factors, namely Cocooning and 99 Lives, had low internal consistency and they were therefore excluded from the study. The study showed that in general respondents agreed with the consumer trends of Faith Popcorn, meaning that these consumer trends occurred among the study population. It was also found that for certain consumer trends, some biographical variables displayed specific effect sizes, which could be significant in practice. The research results indicated that the consumer trends which were under investigation in this study, occurred among the respondents, thus positively answering the research question, as mentioned previously in this abstract. Marketers can apply the knowledge produced by this research into directing their creative approaches to specific market segments in order to include message content about the consumer trends. Some recommendations were made for including message content about consumer trends in order to address consumers’ lifestyle needs more effectively in IMC. Recommendations were made for future research, such as, inter alia: (i) a descriptive study incorporating additional trends of Popcorn into an investigation; (ii) a comparative study within other industries in South Africa to determine whether any similarities in consumer trends can be determined; (iii) a qualitative research investigation explaining the occurrence/non-occurrence of Faith Popcorn’s trends could also provide valuable information; (iv) an explorative study to identify alternative consumer trends among a similar sample frame; (v) an investigation into the applicability of these trends within an organisation’s IMC strategy, leading to more effective market segmentation and consequently better results; and (vi) a qualitative investigation into the relevance of consumer trend analysis in the formulation of corporate strategy.
Dissertation (M.A. (Integrated Marketing Communication))--University of the Free State, 2007
Keywords: Marketing -- South Africa -- Potchefstroom -- Attitudes; Consumer behavior -- South Africa -- Potchefstroom; Consumer-centric orientation; Consumer trends; Customer; Market segmentation; Integrated marketing communication (IMC); Organisation